Time, space, stars & man : the story of the big bang - Woolfson, Michael M. (Michael Mark) (Imperial College Press ; Distributed by World Scientific Pub., 2008)
Most well-read, but non-scientific, people will have heard of the term "Big Bang" as a description of the origin of the Universe. They will recognize that DNA identifies individuals and will know that the origin of life is one of the great unsolved scientific mysteries. This book brings together all of that material. Starting with the creation of space and time - known as the Big Bang - the book traces causally related steps through the formation of matter, of stars and planets, the Earth itself, the evolution of the Earth's surface and atmosphere, and then through to the beginnings of life an.